Conspiratorial Beliefs and Cognitive Styles: An Integrated Look on Analytic Thinking, Critical Thinking, and Scientific Reasoning in Relation to (Dis)trust in Conspiracy Theories - Gjoneska, Biljana (Frontiers in Psychology, 2021)
The tendency to believe in conspiracy theories (implying secret and malevolent plots by scheming groups or individuals), incites growing decennial interest among psychological researchers (exploring the associated personality traits, worldviews and cognitive styles of people). The link between the conspiratorial beliefs and the cognitive styles remains of particular interest to scholars, because it requires integrated theoretical considerations. This perspective article will focus on the relationship between the propensity to (dis)trust conspiracy theories and three cognitive styles: analytic thinking, critical thinking and scientific reasoning. Analytic thinking (inclination toward slow and effortful processing of information to mitigate biases and reach objective understanding of facts), is a well-studied concept in the context of conspiratorial beliefs, while the negative mutual relationship seems well-evidenced. Inversely, the evidence on the link with the critical thinking (readiness to consider, reason, appraise, review and interpret facts to update existing beliefs) remains accidental. Finally, scientific reasoning (ability to apply principles of scientific inquiry to formulate, test, revise and update knowledge in accordance with new evidence), is a least studied concept in the psychological research on conspiracy theories. The present article will: a) revise the (lack of) scientific consensus on the definitional and conceptual aspects (by providing theoretical framework); b) summarize the state of the art on the subject (by providing overview of empirical evidence); c) discuss directions for future research (especially in relation to the COVID-19 pandemic). An integrated perspective on the relationship between conspiratorial beliefs and cognitive styles of people, may serve to inspire future behavioral interventions.